Створення системи управління "розумними приладами" для нежитлових будівель - Сільченко, М. О. (ХНУРЕ, 2023)
This work is dedicated to the «Smart home» topic. The text will describe the current situation with smart devices overall and how existing apps allow you to control them, what problems companies face when try to use existing apps and proposal how to solve those problems